CONTINUOUS GPS NETWORK IN VIETNAM AND RESULTS OF STUDY ON THE TOTAL ELECTRON CONTENT IN THE SOUTH EAST ASIAN REGION - Minh*, Le Huy; Lan, Tran Thi; -Mazaudier, C. Amory; Fleury, R.; Bourdillon, A.; Hu, J.; Hung, Vu Tuan; Thang, Nguyen Chien; Thanh, Le Truong; Thanh, Nguyen Ha (Vietnam Journal of Earth Sciences, 2016)
This study presents the continuous GPS network in Vietnam and the results of the study on time variations of the total electron content (TEC) in the South East Asian equatorial ionization anomaly (EIA) for the 2006-2013 period. In each year we observe a semiannual pattern of TEC diurnal variation in all the stations with its maximum amplitude at the equinox. In both hemispheres, the amplitude of the crest is larger in northern spring equinox than in autumn from 2006 to 2008 (descending phase of solar cycle) and smaller in spring than in autumn from 2009 to 2011 (increasing phase of solar cycle), from 2012-2013 (maximum period of solar cycle) the amplitudes of the crests in spring and autumn are equivalent. We also observe an asymmetry between the amplitude and the position of the two crests of ionization. There is a very high level of correlation between the amplitude of the TEC at the two crests and the sunspot number is approximately equal to 0.9. During the deep solar minimum 2008-2009, the amplitude of crests of ionization becomes small during several months in summer and winter (about 20 TECu). The results show that both crests move more significantly equatorward in winter than in other seasons and there is a tendency for both crests to appear earlier in winter and later in summer. In the solar minimum years, the amplitudes of the crests are minimal; the positions of the crests are nearer the magnetic equator and the crests appear earlier than in other years. References Amory-Mazaudier C.,  Le Huy M., Y. Cohen, V. Doumbia, A. Bourdillon, R. Fleury, B. Fontaine, Ha Duyen C., A. Kobea, P.  Laroche, P. Lassudrie-Duchesne, Le Viet H., Le Truong T., Luu Viet H., M. Menvielle, Nguyen Chien T., Nguyen Xuan A., F. Ouattara, M. Petitdidier, Pham Thi Thu H., Pham Xuan T., P. Philippon, Tran Thi L., Vu Thien H., and P. Vila, 2006. Sun-Earth System Interaction studies over Vietnam: an international cooperative project, Ann. Geophys., 24, 3313-3327. Appleton E., 1946. Two anomalies in the Ionosphere, Nature, 157, 691. Breit G. and M. A. Tuve, 1926. A test of the existence of the conducting layer, Phys. Rev., 28, 554-575. Chakraborty S. K., and R. Hajra, 2008. Solar control of ambient ionization of the ionosphere near the crest of the equatorial anomaly in the Indian zone, Ann. Geophys., 26, 47-57. Chen C.H., J.Y. Liu, K.Yumoto, C.H. Lin and T.W. Fang, 2008. Equatorial ionization anomaly of the total electron content and equatorial electrojet of ground-based geomagnetic field strength, J. Atmos. Solar Terr. Phys., 70, 2172-2183. Duong Chi Cong, 2010. Study on scientific basis and reality of utilizing GPS technology to examine the condition of the ionosphere and the troposphere. Project of Ministry of Natural Resources and Environment. Vietnam Institute of Geodesy and Cartography. http://www.vigac.vn. (in Vietnamese) Huang Y.-N. and K. Cheng, 1996. Solar cycle variations of the equatorial ionospheric anomaly in total electron content in the Asian region, J. Geophys. Res., 101, A11, 24,513-24,520. Huang Y.-N., K. Cheng, and S.-W Chen, 1989. On the equatorial anomaly of the ionosphere total electron content near the northern anomaly crest region, J. Geophys.  Res., 94, A10, 13,515-13,525. Klobuchar J., 1986. Design and characteristics of the GPS ionospheric time-delay algorithm for single frequency users, in Proceedings of PLANS’86 - Position Location and Navigation Symposium, Las Vegas, Nevada, 280-286, 4-7 November, 1986. Komjathy A., L. Sparks, B. D. Wilson, and A. J. Mannucci, 2005. Automated daily processing of more than 1000 ground-based GPS receivers for studying intense ionospheric storms, Radio Science, VOL. 40, RS6006, doi:10.1029/2005RS003279. Le Huy M., C. Amory-Mazaudier, R. Fleury, A. Bourdillon, P. Lassudrie-Duchesne, L. Tran Thi, T. Nguyen Chien  and T. Nguyen Ha, P. Vila, 2014. Time variations of the total electron content in the Southeast Asian equatorial ionization anomaly for the period 2006-2011, Advances in Space Research, 54, 355-368,  http://dx.doi.org/10.1016/-j.asr.2013.08.03. Le Huy Minh, A. Bourdillon, P. Lasudrie-Duchesne, R. Fleury, Nguyen Chien Thang, Tran Thi Lan, Ngo Van Quan, Le Truong Thanh, Hoang Thai Lan, Tran Ngoc Nam, 2006. Determination of the ionospheric total electron content in Vietnam through data of GPS stations, Journal of Geology, A269, 54-62. (in Vietnamese) Le Huy Minh, Pham Xuan Thanh, Tran Thi Lan, Nguyen Chien Thang, Nguyen Ha Thanh, Le Truong Thanh, 2010. GPS technology and its application in study on Earth science, Proceedings of Scientific Works on the 35th Anniversary of Vietnam Academy of Science and Technology, Subcommittee: Earth Science, 65-79, ISBN 978-604-913-016-8. (in Vietnamese) Liu J. Y., H. F. Tsai, and T. K. Jung, 1996. Total electron content obtained using the global positioning system, TAO, 7(1), 107-117. Mala S. B., H. P. Joshi, K. N. Iyer, M. Aggarwal, S. Ravindran, and B. M. Pathan, 2009. TEC variations during low solar activity period (2005-2007) near the Equatorial Ionospheric Anomaly Crest region in India, Ann. Geophys., 27, 1047-1057. Mayr H. G., I. Harris, and N. W. Spencer, 1978. Some properties of upper atmosphere dynamics, Rev. Geophys. Space Physics, 16, 539-565. Namba S., and K.-I. Maeda, 1939. Radio wave propagation, 86pp, Corona Publishing, Tokyo. Pham Thi Thu H., C. Amory-Mazaudier, and Le Huy M., 2011. Time variations of the ionosphere at the northern tropical crest of ionization at Phu Thuy, Vietnam, Ann. Geophys., 29, 197-207. Rama Rao P. V. S., S. Gopy Krishna, K. Niranjan, and D. S. V. V. D. Prasad, 2006. Temporal and spacial variations in TEC using simultaneous measurements from the Indian GPS network of receivers during the low solar activity period of 2004-2005, Ann. Geophys., 24, 3279-3292. Rishbeth H. and I. C. F. Muller-Wodarg, 2006. Why is there more ionosphere in January than in July? The annual asymmetry in the F2-layer, Ann. Geophys., 24, 3293-3311. Torr M. R. and D. G. Torr, 1973. The seasonal behavior of the F2-layer of the ionosphere, J. Atmos. Terr. Phys., 35, 2237-2251. Tsai, H.-F., J.-Y. Liu, W.-H. Tsai and C.-H. Liu, 2001. Seasonal variations of the ionospheric total electron content in Asian equatorial anomaly regions, J. Geophys. Res., 106, A12, 30363-30369. Walker G. O., J. H. K. Ma, and E. Golton, 1994. The equatorial ionospheric anomaly in electron content from solar minimum to solar maximum for South East Asia, Ann. Geophys., 12, 195-209. Wu C. C., C. D. Fry, J. Y. Liu, K. Liou and C. L. Tseng, 2004. Annual TEC variation in the equatorial anomaly region during the solar minimum: September 1996-August 1997, J. Atmos. Sol. Terr. Phys., 66, 199-207. Wu C. C., K. Liou, S. J. Shan, and C. L. Tseng, 2008. Variation of ionospheric total electron content in Taiwan region of the equatorial anomaly from 1994-2003, Adv. Space Res., 41, 611-616. Zhao B., W. Wan, L. Liu, Z. Ren, 2009. Characteristics of the ionospheric total electron content of the equatorial ionization anomaly in the Asian-Australian region during 1996-2004, Ann. Geophys., 27, 3861-3873.